Disoriented Liberalism: Ortega y Gasset in the Ruins of Empire. (October 2019) - Dinnin, Alec
The fraught ideological relationship between liberalism and imperialism has been theorized primarily through the British, French, and American empires. This article moves beyond the experiences of these "great powers" by turning to Spain and its preeminent twentieth-century liberal thinker, José Ortega y Gasset. Unlike his British, French, and American counterparts, Ortega articulated liberalism not to promote or defend the forging of empire but rather to cope with the disorienting effects of its unequivocal loss in the wake of the Spanish–American War. The experience of imperial loss, I argue, informed Ortega's call for a "new liberalism" that could enable Spain's national and cultural renewal. Reading Ortega's thought in this context thus reveals the lasting impact that imperial dispossession can have upon certain strands of liberalism. It also suggests that, in order to fully capture the relationship between liberalism and empire, it is necessary to incorporate a wider range of historical sources and imperial trajectories.